PENERAPAN ANALISIS KONJOIN DALAM MENENTUKAN PERSEPSI SISWA SMA NEGERI 1 MERAUKE TENTANG KARAKTERISTIK GURU MATEMATIKA - Teguh Santoso; Maria F. V. Ruslau; Dessy Riski Suryani (Musamus University, 2018)
This research aims to know the characteristic of ideal mathematics teacher according to student of SMA Negeri 1 Merauke. This research is quantitative research. The sampling technique used was stratified proportional random sampling technique and obtained 256 students as sample. Data collection techniques used is the spread of questionnaires, then data from the questionnaire were analyzed using conjoint analysis with full profile method and orthogonal array. The results showed that the characteristics of mathematics teachers desired by students are teachers of male sex, have age between 46-55 years, then have a relaxed but serious teaching style, using unconventional learning method, teacher convey mathematics material accompanied by its application in daily life, then have high spirit of teaching and able to use technology in learning well, interaction between teacher with active student.